Cognitive fit: an empirical study of recursion and iteration - Sinha, A.P.; Vessey, I. (IEEE transactions on software engineering, 1992)
A laboratory experiment was conducted to assess the basic theory and extensions to the theory for recursive tasks across programming languages. The experiment used 34 LISP and 48 PASCAL computer science students in two repeated measures designs. Findings of the study are reported and analyzed. The results strongly suggest that investigation of programming constructs should take place in the context of specific programming languages. Since a number of languages provide similar kinds of programming constructs, it is difficult for programmers to choose those implementations that best suit their needs. One way of encouraging the use of desirable constructs would be to develop languages adapted to certain types of tasks. Such an approach would inherently lead to cognitive fit and the attendant performance benefits would be realized.< >